PETROLOGI DAN ESTIMASI SUMBER DAYA BATUAN TANAH URUG PADA WILAYAH EKSPLORASI DAERAH TAROKAN, KAB. KEDIRI, JAWA TIMUR - Fajar Rizki Widiatmoko; Yazid Fanani; Yohanes Jone; Simela Talaohu; Muhammad Agus Irwanto; I Wayan Koko Suryawan; Mega Mutiara Sari; Ratih Hardini Kusuma Putri (KURVATEK, 2022)
Kediri Regency is a potential area for mining minerals. One of the rock excavation materials found in Kediri Regency is the type of andesite and backfill. Backfill is a mineral as a result of weathering of the parent rock, which is rich in andesite fragments and silica elements. This research was conducted at the exploration location of Tarokan Village, Tarokan District, Kediri Regency. The study was conducted using petrological analysis to obtain rock types and estimates of the availability of these minerals at the research site. Based on the results of petrological analysis, it shows that the sample is a type of backfill and andesite. However, the presence of all samples was dominated by samples of backfill that were present in abundance in as much as 98 % of the total exploration area. Based on the results of the estimation of backfill resources from geological modeling and volumetric calculations from the triangulation concept at an elevation of 110-72 mdpl, the measured resource of the Sandy Tuff unit (TU) has a volume of 2,514,150 m3, based on the results of the analysis of the average rock density of 2.172 g/cm3, the tonnage of the sandy tuff unit is 5,460,734 tons, with the tonnage of backfill from tuff 4,203,659 tons, and andesite tonnage 1,257,075 tons.